Resident perception of Obstetrics and Gynecology(OBGYN) residency pelvic anatomy curriculum: a national study - Sharonne Holtzman; Lily McCarthy; Isabel S. Chess; Yara Sifri; Farida Nentin; Frederick Friedman (BMC Medical Education)
Abstract Background Pelvic Anatomy is an integral part of the educational objectives in Obstetrics and Gynecology (OBGYN) residency. As a surgical subspecialty, mastering pelvic anatomy is imperative in performing successful surgical procedures, reducing surgical complications, and improving surgical outcomes. The objective of this study was to conduct a national survey to examine the OBGYN resident perspective on their residency’s pelvic anatomy curriculum. Methods After Institutional Review Board at the Mount Sinai Hospital approval, an 18-question survey was distributed to all 241 ACGME program coordinators to distribute to their residents. The survey was circulated electronically using SurveyMonkey tool and on four different dates including: 11/18/2021, 2/24/2022, 4/11/22, and 5/2/22. All demographic information, training environment and perspective on pelvic anatomy was collected anonymous through the survey. All statistical analysis was done using SPSS 2.0. Results Out of 241 programs, we received responses from 28 programs with a total of 582 possible residents in their respective programs. A total of 180 residents responded to our survey which is a 31.0% response rate. Out of all the residents, 46 (25.84%) were PGY1, 40 (22.47%) were PGY2, 43 (24.16%) were PGY3 and 49 (27.53%) were PGY4. The majority of residents, 172 (95.5%), were between the ages 25–34, and 155 (86.1%) identified as female. The majority, 125 (69.4%), of residency programs were considered academic and 99 (55.0%) of the respondents considered the location of their residency as urban. All ACOG districts were represented in our survey. Throughout their residency training, 104 (58.10%) residents experienced formal education on pelvic anatomy in their residency and 75 (41.90%) did not. In terms of surgical curriculum, 138 (77.53%) participated in a formal surgical simulation curriculum and 40 (22.47%) did not. There were 159 (88.83%) who had protected lecture time that focused on pelvic surgical anatomy, but only 100 (62.9%) residents felt that these lectures were helpful for their education. When residents were asked if they felt that their OBGYN program should have formal time in an anatomy lab from a scale of 1–10, the average answer was 7.5. When the residents were asked if they felt that formal training in anatomy lab would help them become a better surgeon, the average answer was 9.0. For our primary outcome, when ranking their own program from a scale of 1–10, residents felt that their program trained them in all aspects of OBGYN on average of an 8. On multivariable analysis, residents who had formal education on pelvic anatomy as well as those residents who had a surgical simulation curriculum as part of their OBGYN residency felt that their residency program was more likely to adequately train them in all aspects of OBGYN (p < 0.05). Conclusions Pelvic anatomy education is an important topic for residents during their OBGYN training. Only 60% of programs have a formal pelvic anatomy curriculum and 89% had formal lectures on pelvic anatomy, with majority of residents finding pelvic anatomy lectures to be unhelpful for their education. Residency programs should consider adding hands-on, formal anatomy education to their curriculum to adequately train their residents in the field of OBGYN.